Geomorphology and chronology of Late Quaternary dune fields of western Argentina - Tripaldi, Alfonsina (2007)
Stabilized dune fields are common in western Argentina and potentially reflect drought variability in the Late Quaternary. This study focussed on deciphering geomorphic and stratigraphic record of three vegetated dune fields from east to west, San Luis, Médanos Negros and Médanos Grandes, with a mean annual precipitation from ∼ 700 to 91 mm. Optically stimulated luminescence single-aliquot regeneration protocols yield ages on eolian quartz grains, constraining depositional events. The San Luis dune field, the wettest area, exhibits evidence for repeated activation during the last glaciation, ca. 33-20 ka, generally coincident with regional loess deposition These dunes were locally reformed in the past 100 years which is apparently coincident with intensified agrarian use and drying in the late 19th and early 20th century. The two driest and western-most dune fields, Médanos Negros and Médanos Grandes, show reactivation at ca. 2.5 ka 0.9 and 0.5 ka; and ca. 4.3-4, 2.1 and 0.6-0.4 ka, respectively. Eolian depositional events at ca. 2.5-2.1 ka and 0.6-0.4 ka may be coeval for Médanos Grandes and Negros dune fields. Sustained drought conditions conducive for eolian activity is associated with warmer sea surface temperatures in the South Atlantic, a weakened South American Convergent Zone and a dispersed and southeasterly flow of tropical moisture from the Low Level Chaco Jet. This nascent analysis indicates drought variability beyond historic observations with potentially at least four dune reactivation events in the past ca. 4.5 ka.